Lipases produzidas por fungos derivados de ambiente marinho: otimização, purificação e caracterização bioquímica - Videira, Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Lipases are hydrolases (triacylglycerol acylhydrolases EC 3.1.1.3) capable of hydrolyzing carboxyl esters of long-chain acylglycerol release mono- or diacyglycerol, free glycerol and fatty acid. In addition, the lipases are effective for synthesis reactions such as esterification, glycerolysis, transesterification and aminolysis, this capability related to the displacement of the equilibrium of the reaction towards synthesis or hydrolysis inherent in the concentration of water present in the medium, the characteristic that makes biocatalysts very versatile, with important biotechnological applications. Such as food, detergents, pharmaceutical, textile, leather, paper and cosmetics industries. This work aimed to identify six species of fungi that produce lipase, optimize the production of this enzyme by lineage selected and purify and characterize partially the lipase produced in optimal condition. Enzyme activity was determined after submerged cultures, aiming to increase enzyme production. The factors measured in this optimization process of lipase production were: mineral components, time of cultivation, source of carbon and nitrogen and their concentration, pH and inoculum. The use of molecular markers allowed us to identify the six lipolytic fungi until species, except for strain Fusarium sp. CBMAI 1227. The methodology of screening of fungi for the production of lipase in neutral medium allowed the selection of the isolated Trichodemra harzianum CBMAI 1229 as best producer. The evaluation of improved cultivation conditions was assayed by lipase activity, determined through hydrolysis releasing íon ρ-nitrofenol (pNP) of ρ-nitrophenyl-palmitate (pNPP) as substrate synthetic at 37 °C. The best condition for lipase production (231,58 ± 35,59 U mL-1) was reached after 120 hours of cultivation, 25 °C and 150 rpm in medium mineral Olson & Johnson (1948), suplemented with sunflower oil 3,0% (v/v), peptone 2,0% (w/v), yeast extract 0,2%...

Lipases são hidrolases (triacilglicerol acil hidrolases, EC 3.1.1.3) capazes de hidrolisar ésteres carboxílicos de cadeia longa liberando monoacilgliceróis, diacilgliceróis, ácidos graxos e glicerol. Em adição, as lipases são eficientes em reações de síntese como esterificação, glicerólise, aminólise e transesterificação, essa capacidade relacionada ao deslocamento do equilíbrio da reação no sentido de hidrólise ou síntese dependendo da concentração de água presente no meio, característica que as tornam biocatalizadores muito versáteis, com importantes aplicações biotecnológicas, como em indústrias de alimentos, detergentes, farmacêutica, couro, têxtil, cosméticos e papel. O presente trabalho objetivou identificar as seis espécies de fungos lipolíticos, otimizar a produção dessa enzima pela linhagem selecionada, bem como purificar e caracterizar parcialmente a lipase produzida em condição otimizada. A atividade lipase foi determinada após cultivos submersos, objetivando o aumento da produção da enzima. Os fatores avaliados no processo de otimização da produção de lipase foram: meios minerais, tempo de cultivo, fontes de carbono e nitrogênio e suas concentrações, pH e inóculo. A avaliação das melhores condições de cultivo foi realizada pela atividade lipase, determinada pelo íon ρ-nitrofenol (pNP) liberado na hidrólise do substrato sintético ρ-nitrofenil palmitato a 37 °C. O uso de marcadores moleculares permitiu identificar os seis fungos lipolíticos até espécie, exceto para a linhagem Fusarium sp. CBMAI 1227. A metodologia de triagem dos fungos para produção de lipase em meio neutro permitiu a seleção do isolado Trichodemra harzianum CBMAI 1229 como melhor produtor. A melhor condição para produção de lipase (231,58 ± 35,59 U mL-1) foi alcançada após 120 horas de cultivo a 25 °C e 150 rpm de agitação utilizando meio mineral Olson e Johnson (1948), suplementado com óleo...
Keywords: Enzymes; Enzimas; Fungos; Lipase; Bioquímica